Szkolnictwo wyższe w Ukrainie w czasie wojny: zmiana roli i funkcji wykładowców - Hordiichuk, Olha (Rocznik Pedagogiczny, 2022)
The aim of the article is providing the comprehensive analysis of the peculiarities of the functioning of higher education in Ukraine in the conditions of a full-scale war (from February 24, 2022). The transformation of the role and tasks of university lecturers during the war is emphasized. The article delivers the research results of students’ opinion on this issue, their analysis with reference to everyday practice.